Two novel lanthanide(III) organic frameworks based on a biphenyltetracarboxylate ligand: synthesis, structure and magnetic and luminescence properties. Issue 3 (27th February 2018) - Hao, Hongguo; Wang, Yuchen; Yuan, Suxian; Li, Dacheng; Sun, Junshan
Abstract : Two new two‐dimensional lanthanide coordination polymers have been synthesized under solvothermal conditions from biphenyl‐3, 3′, 5, 5′‐tetracarboxylic acid (H4 bpt) and Ln(NO3 )3 ·6H2 O (Ln = Tb and Eu). Topological analysis shows that the bpt 4− ligand and the {Ln2 (μ2 ‐CH3 COO)2 } building unit could be considered as a (4, 6)‐connected network withsql topology. A magnetic investigation shows the presence of antiferromagnetic interactions in the Tb compound. Abstract : Two new two‐dimensional lanthanide coordination polymers, namely poly[[tetra‐μ2 ‐acetato‐tetraaquabis(μ4 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)tetrakis(dimethylacetamide)tetraterbium(III)] pentahydrate], {[Tb4 (C16 H6 O8 )2 (C2 H3 O2 )4 (C4 H9 NO)4 (H2 O)4 ]·5H2 O} n, (1), and poly[[tetra‐μ2 ‐acetato‐tetraaquabis(μ5 ‐biphenyl‐3, 3′, 5, 5′‐tetracarboxylato)tetrakis(dimethylacetamide)tetraeuropium(III)] tetrahydrate], {[Eu4 (C16 H6 O8 )2 (C2 H3 O2 )4 (C4 H9 NO)4 (H2 O)4 ]·4H2 O} n, (2), have been synthesized from biphenyl‐3, 3′, 5, 5′‐tetracarboxylic acid (H4 bpt) and Ln(NO3 )3 ·6H2 O (Ln = Tb and Eu) under solvothermal conditions. Single‐crystal X‐ray structure analysis shows that the two compounds are isostructural and crystallize in the monoclinic P 21 / n space group. The crystal structures are constructed from bpt 4− ligands (as linkers) and {Ln2 (μ2 ‐CH3 COO)2 } building units (as nodes), which topological analysis shows to be a (4, 6)‐connected network withsql topology. Compounds (1) and (2) have been characterized by elemental analysis, IR spectroscopy, powder X‐ray diffraction (PXRD), thermogravimetric analysis (TGA) and fluorescence analysis in the solid state. In addition, a magnetic investigation shows the presence of antiferromagnetic interactions in compound (1).